Measuring Synchrony in Task-based Dialogues - VOGEL, CARL; Reverdy, Justine (ISCA, 2017)
In many contexts from casual everyday conversations to formal discussions, people tend to repeat their interlocutors, and themselves. This phenomenon not only yields random repetitions one might expect from a natural Zipfian distribution of linguistic forms, but also projects underlying discourse mechanisms and rhythms that researchers have suggested establishes conversational involvement and may support communicative progress towards mutual understanding. In this paper, advances in an automated method for assessing interlocutor synchrony in task-based Human-to-Human interactions are reported. The method focuses on dialogue structure, rather than temporal distance, measuring repetition between speakers and their interlocutors last n-turns (n = 1, however far back in the conversation that might have been) rather than utterances during a prior window fixed by duration. The significance of distinct linguistic levels of repetition are assessed by observing contrasts between actual and randomized dialogues, in order to provide a quantifying measure of communicative success. Definite patterns of repetitions where identified, notably in contrasting the role of participants (as information giver or follower). The extent to which those interacted sometime surprisingly with gender, eye-contact and familiarity is the principal contribution of this work.
Proceedings of the 18th Annual Conference of the International Speech Communication Association (INTERSPEECH2017)
Keywords: Alignment; Human-human interaction; Computational linguistics; Repetitions; Dialogue structure; Creative Technologies; Digital Humanities; Intelligent Content & Communications; Computational linguistics; Discourse & Dialogue; Philosophy of Language